GLOBALISASI DAN MASYARAKAT MENUA TIONGKOK: PARIWISATA DAN POTENSI LANSIA - Erlita Tantri (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2018)
China is one of the countries that has a large number of elderly in the world. In 2016, China has 230.8 million elderly people and it is predicted that 40 percent of China's population in 2050 is elderly. Although the elderly are often regarded as a burden for the State and the family, but fortunately the elderly also have substantial potency, especially in the economic realm. One of the Chinese elderly potency is in tourism. In tourism, elderly travel activities are followed by the development of technology and services that related to tourism. This paper tries to observe the potency of Chinese elderly in their leisure time with travel. Filling leisure time with a tour not only can improve the health conditions of the elderly that affect to longer life expectancy, but also stimulate the development of silver hair industry in tourism for China and other countries.Keywords : elderly, leisure time, ChinaAbstrakTiongkok adalah salah satu Negara yang memiliki jumlah lansia yang cukup besar di dunia. Tahun 2016 saja Tiongkok telah memiliki 230,8 juta jiwa lansia dan tahun 2050, diprediksikan 40 persen penduduk Tiongkok adalah lansia. Meskipun lansia kerap dianggap sebagai beban bagi Negara dan keluarga, namun lansia juga memiliki potensi yang cukup besar terutama dalam aspek ekonomi. Salah satu potensi lansia Tiongkok adalah pada sektor pariwisata. Dalam pariwisata, kegiatan berwisata lansia diikuti dengan berkembangnya teknologi dan jasa yang berkaitan dengan turisme. Tulisan ini berupaya melihat potensi lansia Tiongkok dalam mengisi waktu luang dengan berwisata. Mengisi waktu luang dengan berwisata bukan hanya dapat memperbaiki kondisi kesehatan lansia yang berdampak pada harapan hidup yang semakin panjang, namun juga merangsang berkembangnya industri lansia terkait pariwisata di Tiongkok dan Negara lain.Kata kunci : Lansia, waktu luang, pariwisata, Tiongkok